New Perspectives in Phenomenological Psychopathology: Its Use in Psychiatric Treatment - Messas, Guilherme; Tamelini, Melissa; Mancini, Milena; Stanghellini, Giovanni (Frontiers in Psychiatry, 2018)
Phenomenological psychopathology is as a body of scientific knowledge on which the clinical practice of psychiatry is based, a method to assess the patient’s abnormal experiences from their own perspective, and more importantly, a science responsible for delimiting the object of psychiatry. Recently, the frontiers of phenomenological psychopathology have expanded to the productive development of therapeutic strategies that target the whole of existence in their actions. In this article, we present an overview of the current state of this discipline, summing up its main consolidated concepts, and highlighting its importance to clinical psychiatry today. Phenomenological psychopathology understands mental disorders as modifications of the main dimensions of the life-world: lived time, lived space, lived body, intersubjectivity and selfhood. Abnormal mental phenomena are the expression of a more or less pronounced dialectical modifications of the proportions of certain domains of the lived experience. The far-reaching relevance of the concepts of proportion and dialectics for the clinical agenda is explored. The article presents two contemporary models for clinical practice based on phenomenological psychopathology: Dialectical-proportional oriented approach and Person-centered dialectic approach (P.H.D. method). The main characteristics of these approaches are presented, as well as the new perspectives they bring to the challenges of psychiatric care in the twentieth-first century.